Preparation and Characterization of Biomass Briquettes Using Corncob, Rice Husk, Sawdust and Coco Peat - Lal, Shankar; Koumary, Nitin Kumar; Gilhare, Sanjay Kumar; Singh, Gajendra; Ganjeer, Indu (International Journal of Economic Plants, 2025)
The experiment conducted during July, 2023, at the college of agricultural engineering, IGKV Raipur Chhattisgarh, India focused on converting corncob, rice husk, sawdust, and coco peat into biomass briquettes as an alternative energy source to fossil fuels. Various compositions of biomass briquettes were prepared and characterized based on their physical and thermal properties, as well as their burning capacity using the Water Boiling Test (WBT). Among the nine compositions tested, sample L4 (a 50:50 ratio of corncob and sawdust) showed the best results, with a bulk density of 610 kg m-3, moisture content of 2.75%, and solid content of 98.1%. Proximate and ultimate analyses were conducted to determine the composition and properties of the briquettes. Sample L4 exhibited the highest fixed carbon content at 47.95%, and the lowest ash content at 3.69%, which is beneficial for combustion efficiency. In contrast, the corncob and coco peat combination in sample L9 (40:60 ratio) had the highest volatile matter at 62.33%, promoting easy ignition. The ultimate analysis of sample L4 revealed an elemental composition of 57% oxygen, 36% carbon, 6% hydrogen, and around 1% nitrogen, with a thermal efficiency of 28%. During the WBT, sample L4 evaporated an average of 210.42 ml of water, and its calorific value was the highest among all samples at 18 MJ kg-1. The study concluded that sample L4, due to its favorable properties, is a promising candidate for alternative energy applications.